Rumpelstiltskin is a thing of the past: Innovation Practices for creating service innovations - Möslein, Kathrin; Neyer, Anne-Katrin; Rau, Christiane (Methods in Service Innovations: Current Trends and Future Perspectives, 2012)
In recent years there has been a growing tendency to regard service research as an independent academic discipline. However, the establishment of thereof is closely intertwined with methodological issues. But, What methodological foundations is the discipline built on? The book, which focuses on the field of service innovation, was launched precisely in order to study the discipline’s methodological foundations and the need to develop and modify specific service research methods in the context of specific examples.
WiSo-Import:2015-04-20:4298